2016
DOI: 10.1097/ccm.0000000000001965
|View full text |Cite
|
Sign up to set email alerts
|

Defining Futile and Potentially Inappropriate Interventions: A Policy Statement From the Society of Critical Care Medicine Ethics Committee

Abstract: The Society of Critical Care Medicine supports the seven-step process presented in the multiorganization statement. This statement provides added guidance to clinicians in the ICU environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(70 citation statements)
references
References 57 publications
1
65
0
4
Order By: Relevance
“…They also introduced the concept of potentially inappropriate treatment (PIT) for the more value-laden situations when there is doubt about whether goals were achievable or in the patient’s best interest [10]. There is an ongoing discussion about how potentially inappropriate interventions should be understood in TBI [37, 38]. The Society of Critical Care Medicine Ethics Committee has suggested that “ ICU interventions should generally be considered inappropriate when there is no reasonable expectation that the patient will improve sufficiently to survive outside the acute care setting, or when there is no reasonable expectation that the patient’s neurologic function will improve sufficiently to allow the patient to perceive the benefit of treatment” [38].…”
Section: Discussionmentioning
confidence: 99%
“…They also introduced the concept of potentially inappropriate treatment (PIT) for the more value-laden situations when there is doubt about whether goals were achievable or in the patient’s best interest [10]. There is an ongoing discussion about how potentially inappropriate interventions should be understood in TBI [37, 38]. The Society of Critical Care Medicine Ethics Committee has suggested that “ ICU interventions should generally be considered inappropriate when there is no reasonable expectation that the patient will improve sufficiently to survive outside the acute care setting, or when there is no reasonable expectation that the patient’s neurologic function will improve sufficiently to allow the patient to perceive the benefit of treatment” [38].…”
Section: Discussionmentioning
confidence: 99%
“…Critical care management has been understood for more than two decades to be a trial of management, with ethically justified, beneficence-based criteria for its initiation and discontinuation (Consensus statement of the Society of Critical Care Medicine's Ethics Committee regarding futile and other possibly inadvisable treatment 1997; Kon et al 2016). Critical care management should be initiated when, in deliberative (evidence-based, rigorous, transparent, and accountable) clinical judgment, it is reliably predicted to result in the clinical benefit of reducing the risk of mortality and preserving at least some interactive capacity, that is, when initiating critical care management is medically reasonable.…”
Section: Guest Editorialmentioning
confidence: 99%
“…( 3 , 5 ) Even in patients with severe, advanced diseases, ICU utilization during terminal hospitalization may occur in up to 50% of cases, ( 6 ) and much of that care may be seen as nonbeneficial or inconsistent with patients' values and preferences. ( 7 ) Moreover, potentially inappropriate ICU admissions ( 8 ) may increase the strain on the allocation of scarce critical care resources. ( 9 - 11 )…”
Section: Introductionmentioning
confidence: 99%